Effect‐Directed Synthesis of a Dithioacetal Tyrosinase Inhibitor - Escalante, Andrea Marta (2024)
Traditional methods for discovering bioactive compounds can be time-consuming and resource-intensive, often requiring extensive synthesis and evaluation. To address these challenges, thisstudy combines TLC-based assays with dithioacetal mixture-library preparation, enabling rapid and effective bioactivity screening. Tyrosinase, an enzyme crucial for melanin production and fruitbrowning, serves as a significant therapeutic target in this context. Despite the substantial potential of sulfur-containing compounds in medicinal chemistry, the use of dithioacetals in drug discoveryremains limited. In this study, two small libraries of dithioacetals, comprising more than 150 compounds, were prepared as mixturelibraries and screened on TLC by directly measuring tyrosinase activity on the plate surface. This approach facilitated the efficient preparation and identification of a potent, simple, and readily accessible dithioacetal inhibitor of tyrosinase, with the entire process being conducted on a low milligram scale.